История Северо-Восточной Азии XIX – начала ХХ веков в исследованиях И.И. Попова - ИВАНОВ, Александр Александрович; ЕВДОКИМОВ, Дмитрий Максимович; КРУЖАЛИНА, Анастасия Алексеевна (Гуманитарные исследования в Восточной Сибири и на Дальнем Востоке, 2025)
The article presents an overview of the research and publications of Ivan Popov (1862–1942), a historian, member of «Narodnaya Volya» and journalist, dedicated to the history of the Russian Far East, China, Manchuria and Mongolia of the late XIXth and early XXth century. Popov’s works introduce readers to the features of state building in Asian countries, the socio-economic development of the peoples inhabiting the region, their religious culture and external relations. The authors note that Popov’s scientific legacy shows the influence of the ideas of Siberian regionalism and liberal movement.